Cynometra cauliflora Linn. Attenuates metabolic abnormalities in high-fat diet-induced obese mice - Seyedan, Atefehalsadat; Mohamed, Zahurin; Alshagga, Mustafa Ahmed; Koosha, Sanaz; Alshawsh, Mohammed Abdullah (Elsevier, 2019)
Ethnopharmacological relevance: Cynometra cauliflora Linn. belongs to the Fabaceae family and is known locally in Malaysia as nam-nam. Traditionally, a decoction of the C. cauliflora leaves is used for treating hyperlipidemia and diabetes. Aim of the study: This study aims to investigate the anti-obesity and lipid lowering effects of ethanolic extract of C. cauliflora leaves and its major compound (vitexin) in C57BL/6 obese mice induced by high-fat diet (HFD), as well as to further identify the molecular mechanism underlying this action. Methods and material: Male C57BL/6 mice were fed with HFD (60% fat) for 16 weeks to become obese. The treatment started during the last 8 weeks of HFD feeding and the obese mice were treated with C. cauliflora leaf extract at 200 and 400 mg/kg/day, orlistat (10 mg/kg) and vitexin (10 mg/kg). Results: The oral administration of C. cauliflora (400 and 200 mg/kg) and vitexin significantly reduced body weight, adipose tissue and liver weight and lipid accumulation in the liver compared to control HFD group. Both doses of C. cauliflora also significantly (P ≤ 0.05) decreased serum triglyceride, LDL, lipase, IL-6, peptide YY, resistin levels, hyperglycemia, hyperinsulinemia, and hyperleptinemia compared to the control HFD group. Moreover, C. cauliflora significantly up-regulated the expression of adiponectin, Glut4, Mtor, IRS-1 and InsR genes, and significantly decreased the expression of Lepr in white adipose tissue. Furthermore, C. cauliflora significantly up-regulated the expression of hypothalamus Glut4, Mtor and NF-kB genes. GC-MS analysis of C. cauliflora leaves detected the presence of phytol, vitamin E and β-sitosterol. Besides, the phytochemical evaluation of C. cauliflora leaves showed the presence of flavonoid, saponin and phenolic compounds. Conclusion: This study shows interesting outcomes of C. cauliflora against HFD-induced obesity and associated metabolic abnormalities. Therefore, the C. cauliflora extract could be a potentially effective agent for obesity management and its related metabolic disorders such as insulin resistance and hyperlipidemia. © 2019 Elsevier B.V.